Do shareholders or stakeholders appropriate the rents from corporate diversification? The influence of ownership structure - DAVID, Parthiban (Institutional Knowledge at Singapore Management University, 2010)
Prior work on the performance consequences of corporate diversification has treated all powerful owners as seeking the same benefits from diversification (i.e, higher profit rather than growth) and therefore limiting value appropriation by other stakeholders such as employees and managers. In contrast, we distinguish between domestic "relational" owners and foreign "transactional" owners in Japanese corporations. Although transactional owners do indeed prioritize profitability when diversifying, relational owners primarily seek growth rather than profits from diversification. Furthermore, relational owners also allow managers and employees to appropriate more of the rents arising from diversification than do transactional owners.